EKSISTENSI PERBANKAN SYARIAH SEBAGAI NADZIR DALAM PENGEMBANGAN DAN PENGELOLAAN WAKAF UANG PERSPEKTIF UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF (Studi Pada PT. Bank Sumut Syariah-Cabang Lubuk Pakam) - Raden Juli Moertiono; M. Yamin Lubis; Mustamam Mustamam (LPPM YPITI, 2021)
Bank Sumut Syariah Lubuk Pakam Branch has not been designated as LKS-PWU. So that PT. Bank Sumut Syariah Lubuk Pakam Branch has not been able to receive and directly manage the cash waqf from muwakif. PT. Bank of North Sumatra Syariah, also has not met the requirements to be recommended as LKS-PWU by BWI. Barriers of PT. Bank Sumut Syariah-Lubuk Pakam Branch in its position as nadzir to manage and develop cash waqf, is PT. Bank Sumut Syariah-Lubuk Pakam Branch is not included as a LKS-PWU appointed by the minister. The efforts of Islamic banks as nadzir are to increase the role of nadzir and the Indonesian Waqf Board as well as Sharia Financial Institutions and also Sharia Business Units. then encouraging the community's interest in implementing cash waqf and also changing the community's paradigm of waqf. Especially for PT. Bank of North Sumatra Syariah-Lubuk Pakam Branch, must meet the requirements as LKS-PWU which have been stipulated by laws and regulations.